Sex differences in hippocampal-dependent memory and the hippocampal lipidome in adolescent rats raised on diets with or without DHA. (May 2023) - Lamontagne-Kam, Daniel M.; Davari, Saeideh; Aristizabal-Henao, Juan J.; Cho, Seungjae; Chalil, Dan; Mielke, John G.; Stark, Ken D.
Highlights: Female rats benefit from dietary DHA more than males in key measures of spatial memory. Females fed DHA had more DHA in hippocampal PE 18:0_22:6, PE P-18:0_22:6, and PE P-16:0_22:6 while maintaining levels of PE 18:0_20:4 in contrast with males fed DHA. Lipidomic profiles of plasmenyl phosphatidylethanolamines may be insightful blood biomarkers of brain DHA status. Abstract: Recent studies suggest the effects of DHA supplementation on human memory may differ between females and males during infancy, adolescence, and early adulthood, but the underlying mechanisms are not clear. As a result, this study sought to examine the spatial memory and brain lipidomic profiles in female and male adolescent rats with or without a DHA-enriched diet that began perinatally with the supplementation of dams. Spatial learning and memory were examined in adolescent rats using the Morris Water Maze beginning at 6 weeks of age and animals were sacrificed at 7 weeks of age to permit isolation of brain tissue and blood samples. Behavioral testing showed that there was a significant diet x sex interaction for two key measures of spatial memory (distance to zone and time spent in the correct quadrant during the probe test), with female rats benefiting the most from DHA supplementation. Lipidomic analyses suggest levels of arachidonic acid (ARA) and n-6 docosapentaenoic acid (DPA) containing phospholipid species were lower in the hippocampus of DHA supplemented compared with control animals, and principal component analyses revealed a potential dietary treatment effect for hippocampal PUFA. Females fed DHA had slightly more PE P-18:0_22:6 and maintained levels of PE 18:0_20:4 in the hippocampus in contrast with males fed DHA. Understanding how DHA supplementation during the perinatal and adolescent periods changes cognitive function in a sex-specific manner has important implications for determining the dietary requirements of DHA. This study adds to previous work highlighting the importance of DHA for spatial memory and provides evidence that further research needs to consider how DHA supplementation can cause sex-specific changes.